Geneza antropologii politycznej Carla Schmitta - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This text concerns the political anthropology of Carl Schmitt. Schmitt says that man is inherently evil, he is born in evilness. On this thesis he builds their theory of politics and the concept of the authoritarian state. But he nowhere is developing his political anthropology. It does not explain why the man is born evil and does not explain what is the source of this view? The literature about Schmitt’s theory proposes three interpretations: Christian inspiration, lecture of the writings of Thomas Hobbes, fear of Bolshevism. The author examines these three interpretations and proposes his own. The political anthropology of Carl Schmitt is the mixture of orthodox St. Augustine’s teaching, Hobbes’s theory, fear of Communism, perhaps the tribulations of family life.
Keywords: antropologia polityczna; teoria polityczna; autorytaryzm; dyktatura